1989
DOI: 10.1212/wnl.39.7.959
|View full text |Cite
|
Sign up to set email alerts
|

The lesion of multiple sclerosis

Abstract: Increased blood-brain barrier (BBB) permeability, important in the pathogenesis of MS, may be demonstrated as lesion enhancement with high-volume delayed CT (HVDCT). We studied 40 MS patients with history, neurologic examination, HVDCT, and MRI. In addition, 7 of the patients with enhancing CT lesions were followed with serial MRI for up to 3 years and 7 months. In 3 of these patients we repeated the HVDCT. Patients with enhancing lesions on CT were younger, had shorter duration of disease, and had more freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…First, there is a difference in the immunogen used to induce the two diseases, although whole homogenized CNS contains a large amount of MBP and EAE is a T-cell mediated autoimmune disease in which the T-cell antigen is MBP. Second, Gdenhancement is seen in both acute and subacutelchronic lesions in human MS, and can recur later in recrudescent older lesions (47 disease (MR and clinical) than the chronic-progressive group. Thus, the difference in Gd-DTPA enhancement may be influenced by the severity of the disease as observed in the Strain 13 model (38).…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a difference in the immunogen used to induce the two diseases, although whole homogenized CNS contains a large amount of MBP and EAE is a T-cell mediated autoimmune disease in which the T-cell antigen is MBP. Second, Gdenhancement is seen in both acute and subacutelchronic lesions in human MS, and can recur later in recrudescent older lesions (47 disease (MR and clinical) than the chronic-progressive group. Thus, the difference in Gd-DTPA enhancement may be influenced by the severity of the disease as observed in the Strain 13 model (38).…”
Section: Discussionmentioning
confidence: 99%
“…MRI has become a widely utilized tool in the diagnosis and management of MS. 1-3 Typically, T2-weighted and proton density scans are employed, 2 wherein MS plaques appear as bright hyperintense areas. [17][18][19] Recently, a pathologic study has shown that chronic hypointense lesions ("black holes") on T1-weighted scans are caused by tissue destruction, particularly axon loss. 12,13 Depending on the context, lesions are referred to as "active" with the presence of inflammation or ongoing demyelination.…”
mentioning
confidence: 99%
“…Despite data from animal studies and circumstantial clinical evidence from other disease entities such as cardiovascular disease [75], ischemic stroke [77][78][79][80], and dementia [81,82], it has yet to be determined whether statins will be beneficial in MS. Conducting retrospective studies to gather epidemiologic evidence that MS patients treated for hypercholesterolemia benefit from statin treatment has proven to be challenging for several reasons.…”
Section: Retrospective Analysismentioning
confidence: 99%